Immersive Virtual Reality and Persons with Dementia: A Literature Review. Issue 3 (2nd April 2020) - Strong, Joe
ABSTRACT: Dementia of any type is incurable and treatment is primarily focused on slowing its progression and managing symptoms, typically accomplished through a combination of medication and lifestyle factors. Social workers are uniquely positioned to suggest new and innovative strategies for improving the quality of life. Technology opens a variety of options, and virtual reality is one of the more recent additions to the available toolkit. This review describes the state of the literature as it relates to the use of immersive virtual reality technology with persons with dementia. One hundred fifty-eight articles were returned by keyword search, but just three of those used modern virtual reality systems. Each of the three studies found positive results in their respective uses of virtual reality with persons with dementia. VR was well tolerated by participants and engagement was high, though sample sizes were small across studies. Results demonstrated immersive VR is a viable pathway for a variety of novel interventions with this population, but more research using modern immersive devices is required. Social workers in a variety of care settings can build on these early findings and develop an array of novel palliative and leisure-time experiences for this population.